ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN VIDEO ANIMASI TERHADAP PEMAHAMAN KONSEP SISWA KELAS III PADA MATERI PERUBAHAN WUJUD BENDA PEMBELAJARAN IPAS - Putri, Amelia Anisa; Nadiroti Muslihah, Neni; Ayu Febrianti, Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of using animated video-based learning media in improving third-grade students' conceptual understanding of the material on changes in the form of objects in science and technology learning in elementary schools. The background of this study was driven by the low level of students' conceptual understanding of the material on changes in the form of objects, as seen from the lack of student involvement and enthusiasm during the learning process. The approach used was a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the use of animated video media significantly improved students' conceptual understanding. Animated videos attracted students' attention, fostered enthusiasm for learning, and helped them connect the material on changes in the physical state of objects with events in their daily lives. The success of using this media is supported by creative and innovative learning methods, a conducive learning environment, and the availability of adequate technology and learning resources. Thus, animated video media can be used as a strategic alternative to improve the effectiveness of science learning, especially for material on changes in the form of objects in third grade elementary school.